Manajemen Risiko dalam Hubungan Sekolah dan Masyarakat dalam Pengelolaan Dana Komite SMK Darur Roja Cinere Depok - Ukat Suhaedi (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
The management of school committee funds plays an important role in supporting educational sustainability, particularly in private schools. However, inadequate risk management in fund management may lead to conflicts between schools and communities. This study aims to analyze risk management in school–community relationships related to the management of committee funds at SMK Darur Roja Cinere Depok. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observations, and document analysis. The findings reveal that the main risks include a lack of transparency, potential conflicts of interest, and weak reporting and monitoring mechanisms. The school has not yet implemented a structured risk management system, resulting in reactive risk handling. This study concludes that implementing risk management based on transparency, participation, and accountability is essential to strengthen school–community relationships and maintain public trust in educational institutions.